Effect Size Mobile Learning on Student’s 21 st Century Skills - Muhammad Halfi Indra Indra Syahputra; Muhammad Subhan Iswahyudi; Gunawan Ali; Estuhono Estuhono; Tomi Santosa (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine the effect size of mobile learning on students' 21st century skills. This type of research is a meta-analysis research. The research sample came from 13 national and international journals. Data sources came from google scholar, ScienceDirect, Eric, Wiley and ProQuest databases. Data collection techniques in this study were direct observation and documentation. The process of selecting data sources was carried out carefully and systematically. Inclusion criteria are national and international journals indexed by SINTA and Scopus, research must use experimental or quasi-experimental methods, research must have experimental classes with mobile learning models and conventional controls and research has complete data on the value of n, f and t. The data analysis technique is quantitative statistical analysis with the help of the JSAP application. The results of this study concluded that the average effect size value (ES = 0.853) and the N-gain value of 0.60 These findings indicate that the mobile learning model has a high influence on students' 21st century thinking skills. This finding shows that the mobile learning model has a high impact on students' 21st century thinking skills.